Training The Processing Of Tomato Sauce For A Home-Based Business The Scale Of SMES - Sinta, Irada; Nur Ilham, Rico; Kumala Sari, Dewi; M, Mawardati; Khaidir, Khaidir; Ekamaida, Ekamaida (International Review of Practical Innovation, Technology and Green Energy (IRPITAGE), 2021)
The Corona Virus Disease (COVID-19) pandemic which has an impact on the economy is no exception to the community around the UNIMAL Faculty of Agriculture. The COVID-19 pandemic condition in Aceh caused UNIMAL to carry out online/online-based lecture activities according to the direction of the Ministry of Education and Culture. Campus activities with an online system cause students to carry out the learning process from their home area so they are not in the environment around UNIMAL. The regulation of the online learning system due to the Corona Virus Disease (COVID-19) Pandemic which dealt a tremendous blow to the economy of the community around the UNIMAL Faculty of Agriculture as traders in the UNIMAL environment and providers of rental houses for students. Then, the lack of knowledge of housewives in East Reulet about what business prospects can be run and the cleanliness and food safety of processed products that need to be realized for public health are the basis for this activity to be carried out. The location of the community service was taken around the UNIMAL Faculty of Agriculture Institution, namely Gampong Reulet Timur, North Aceh Regency. At the preparation stage, the implementation of activities begins with increasing coordination and synergistic cooperation between the parties involved, namely Academic Activists (Lecturers) and the targeted community groups. The implementation methodology is designed for mentors in the form of a participatory approach and refers to the adult learning process (adult-learning), which consists of: (1) Providing information related to sauce processing, (2) assignment or direct practice of sauce processing.